Limited efficacy of nontreponemal test combined with treponemal test in the initial syphilis screening algorithm. Issue 2 (20th December 2018) - Gambiez, C.; Garet, C.; Choquet, M.; Decroix, V.; Pluquet, E.; Guiheneuf, R.; Castelain, S.
Abstract : Purpose. Various syphilis screening algorithms have been proposed and are now used by many clinical laboratories following the introduction of automated treponemal tests (TTs). In France, the diagnosis of syphilis is based on a TT combined with a nontreponemal test (NTT). The objective of this study was to evaluate the diagnostic impact of NTT on initial syphilis screening at the Amiens University Hospital between January 2013 and December 2016. Methodology. Serum samples sent for syphilis testing were analysed using a treponemal enzyme immunoassay (Siemens IMMULITE 2000 Syphilis Screen) combined with a nontreponemal test. Enzyme immunoassay (EIA)-reactive and/or nontreponemal-reactive samples were titrated to endpoint using the Treponema pallidum particle agglutination test (TPHA). Complementary tests, such as line immunoassay, and medical charts were reviewed to categorize reactive samples into positive or negative syphilis contacts. Results. Among 15 523 initial screening samples, 148 samples (0.95 %) were reactive with the combined TT and NTT, and 335 (2.16 %) and 66 (0.42 %) were reactive with TT or NTT only. Analysis of the 66 discordant results between TT and NTT showed that only 4 sera were reactive with a second-line TPHA, but these results were not confirmed by line immunoassay and patient characteristics. Conclusion. The results of this study show that the combination of NTT and TT for initial screening does not provide any diagnostic gain, but represents additional laboratory work time.